2012
DOI: 10.4489/kjm.2012.40.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of an Antagonistic Endophytic Bacterium Bacillus velezensis CB3 the Control of Citrus Green Mold Pathogen Penicillium digitatum

Abstract: In order to develop environment friendly fungicide for the control of citrus green mold (Penicillium digitatum) using endophytic bacteria, the 21 bacterial isolates were isolated from citrus leaves in seven different orchards in Jeju Province. Among the 21 bacterial isolates, 5 bacterial isolates presented antifungal activity against green mold pathogen P. digitatum. The CB3 isolate, which showed the most strong antagonistic effect, was selected through opposite culture against the pathogen. The rod-shaped, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…97 Application of B. velezensis CB3 cells (1 × 10 6 CFU/mL, 58% disease incidence inhibition; 1 × 10 7 CFU/mL, 58% disease incidence inhibition; 1 × 10 8 CFU/mL, 67% disease incidence inhibition) and supernatant (56% disease incidence inhibition) provided similar efficacies. 98 A suitable explanation for these differences is that not all strains can successfully colonize different hosts, which is in agreement with the conclusion achieved in the Isolation Sources and Colonization Ability section after analyzing the connections between the isolation source and studied host. For example, B. amyloliquefaciens B4 supernatant reduced the disease incidence of P. expansum by 77−85%.…”
Section: Application Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…97 Application of B. velezensis CB3 cells (1 × 10 6 CFU/mL, 58% disease incidence inhibition; 1 × 10 7 CFU/mL, 58% disease incidence inhibition; 1 × 10 8 CFU/mL, 67% disease incidence inhibition) and supernatant (56% disease incidence inhibition) provided similar efficacies. 98 A suitable explanation for these differences is that not all strains can successfully colonize different hosts, which is in agreement with the conclusion achieved in the Isolation Sources and Colonization Ability section after analyzing the connections between the isolation source and studied host. For example, B. amyloliquefaciens B4 supernatant reduced the disease incidence of P. expansum by 77−85%.…”
Section: Application Methodssupporting
confidence: 83%
“…In contrast with the mentioned results, Chen et al indicated that the control of B. cinerea with B. amyloliquefaciens RS-25 was slightly more effective when using cells (61%–87%) than when applying the culture supernatant (55%–87%) and extracts (57%–76%) . Application of B. velezensis CB3 cells (1 × 10 6 CFU/mL, 58% disease incidence inhibition; 1 × 10 7 CFU/mL, 58% disease incidence inhibition; 1 × 10 8 CFU/mL, 67% disease incidence inhibition) and supernatant (56% disease incidence inhibition) provided similar efficacies …”
Section: Application Methodsmentioning
confidence: 88%
“…Bacillus velezensis is widely used as a biocontrol strain ( 1 3 ). Chang et al ( 4 ) reported that B. velezensis SSH100-10 produces iturin A against fungi.…”
Section: Genome Announcementmentioning
confidence: 99%
“…For example, the bacteria Bacillus amyloliquefaciens reduced the growth of 12 fungal species (including Alternaria panax , Botrytis cinera , Colletotrichum orbiculare , Penicillium digitatum , Pyricularia grisea , and Sclerotinia sclerotiorum ), in vitro and in trials with cucumber and pumpkin plants [70]. Bacillus amyloliquefaciens also reduced fungal rot in citrus [71], strawberries [72], and soybeans [73], and B. velenzensis reduced the infection of citrus green mold by the fungus Penicillium digitatum [74]. In field conditions, where continuously mono-cropped tobacco plants had eventually become infected with Fusarium due to pathogen build-up in soil, large-scale treatment of bacteria native to the soil habitat showed a reduction in fungal infection [75].…”
Section: Plant-microbial Interactionsmentioning
confidence: 99%